Apicultural site zonation using GIS and multi-criteria decision analysis - Mohd Noor Maris, Nisfariza; Mansor, Shattri; M. Shafri, Helmi Zulhaidi (Universiti Putra Malaysia Press, 2008)
This paper discusses the application of Geographical Information System (GIS) and Multi-Criteria Decision Analysis (MCDA) technology as a tool to aid decision-making in a case study to locate beekeeping zones in the state of Selangor. The combination of GIS capabilities with MCDM technique provides greater effectiveness and efficiency of decision making while solving spatial decision problems. In this research, land suitability analysis and zoning was carried out with respect to the bee's biotic needs and some other important factors in apiary management. Suitability weighting was determined using the pairwise comparison matrix of the Analytical Hierarchy Process (AHP) and suitability score using Weighted Overlay function in ArcGIS9. The overall consistency ratio value of AHP pairwise comparison was 0.01 which indicates a reasonable level of consistency in the deployment of the pairwise comparisons. The results of the analysis are presented and verified with actual data of the existing apiaries in Selangor. The integration of AHP model with GIS resulted in Non-Suitable, Most Suitable, Moderately Suitable and Suitable beezones. The total Non Suitable Areas (NS) was 34.73%, leaving the remainder as potential areas (65.27%). The remaining are the Most Suitable Areas (S1) 13.72 %, Suitable Areas (S2) of 27.24% and Moderately Suitable Areas of 24.32 %.